The Impact of Boron Carbide Nanoparticle (B4C-NPs) Toxicity on Caenorhabditis elegans Models - Sen-Ting Huang; Erin P. Bulaon; Kai-Jie Yang; Adriana Taw; Lemmuel L. Tayo; Ping-Heng Hsieh; Jen-Hsiung Tsai; Jian-He Lu; Jheng-Jie Jiang; Hsing-Hsien Wu; How-Ran Chao (Toxics)
Boron carbide (B4C) is a widely recognized ceramic prized for its remarkable properties, including exceptional hardness, low density, and excellent chemical and mechanical stability. To date, limited research has explored the possible health risks associated with B4C nanoparticles (B4C-NPs). This study utilized a Caenorhabditis elegans (C. elegans) in vivo model to investigate the toxicological effects of B4C-NPs at concentrations of 40, 80, 160, and 320 mg/L. Larval nematodes were subjected to prolonged exposure, and their locomotion (head thrashing and body bending), reproduction (brood size), development (body length), lifespan, and gene expression (linked to oxidative stress, metal detoxification, apoptosis, and neurotransmitter synthesis) were assessed. Regarding survival rates, lethality was significantly increased to 5.41% at 320 mg/L of B4C-NPs and lifespan was significantly shortened across all concentrations compared with the controls. Development and reproduction showed slight reductions between 40 and 320 mg/L, while locomotion was markedly impaired at the doses from 80 to 320 mg/L. Gene expression related to antioxidants, apoptosis, cell cycle arrest, neurotransmitter synthesis, and metal detoxification rose significantly at 160–320 mg/L in C. elegans, suggesting that B4C-NPs may induce reproductive and neurological toxicity, delay development, reduce lifespan, and potentially cause genotoxicity in C. elegans.